Recent Insights in Petroleum Science and Engineering 2018
DOI: 10.5772/intechopen.71163
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Methods for Polycyclic Aromatic Hydrocarbons and their Global Trend of Distribution in Water and Sediment: A Review

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are major organic pollutants in the environment, which are toxic to humans and biota, given their carcinogenic, mutagenic and teratogenic nature. In this chapter, we carried out an overview of the sources and toxicity of PAHs, their common analytical methods of determination in the water and sediment samples, and also their global trend of distribution, with a view to provide baseline guidance for relevant control authorities. The choice methods for determining these con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 98 publications
(95 reference statements)
0
36
0
Order By: Relevance
“…135 Exposures to PAHs occur in various forms within the SSA region. 1 Polycyclic aromatic hydrocarbons exposure, environmental health outcomes and health risks. Health risks that may arise as a result of exposure to PAHs are dependent on a number of factors including the route, intensity, and duration of exposure, individual susceptibility, age at exposure, gender, and immune system capability, among others.…”
Section: Polycyclic Aromatic Hydrocarbon Exposure and Health Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…135 Exposures to PAHs occur in various forms within the SSA region. 1 Polycyclic aromatic hydrocarbons exposure, environmental health outcomes and health risks. Health risks that may arise as a result of exposure to PAHs are dependent on a number of factors including the route, intensity, and duration of exposure, individual susceptibility, age at exposure, gender, and immune system capability, among others.…”
Section: Polycyclic Aromatic Hydrocarbon Exposure and Health Outcomesmentioning
confidence: 99%
“…For a number of years now, the problem associated with environmental pollution caused by the release of polycyclic aromatic hydrocarbons (PAHs) into the environment has been worsened by a number of other anthropogenic activities. These include the increasing levels of artisanal refining activities for reasons of survival and financial gain, intense oil exploration, [1][2][3][4] the use of leaded petrol, and poor attitude toward dumping and burning of toxic waste. 5 Others include the occurrence of forest fires, 6 wood combustion, 7 local food processing practices, for example, in smoked fish, 8,9 emissions from combustion engines, and the overdependence on fossil fuels.…”
Section: Introductionmentioning
confidence: 99%
“…However, PAH ratios do change remarkably from the source of pollution to the environmental media under study through existing differences in water solubility and volatility between two PAHs of the same molecular weight, thus making the identified sources less accurate (Biache et al 2014;Wang et al 2016). This situation is also common with the use of LMW/HMW PAH diagnostic ratios, as LMW PAHs are known to be very unstable due to the influence of environmental factors such as photodegradation and volatilization, making them highly affected by flow mechanisms in the aquatic environment (Adeniji et al 2017). These factors, therefore, make the PAH sources identified by studies which used PAH diagnostic ratios less robust.…”
Section: Limitations Of Studymentioning
confidence: 99%
“…Wang and other researchers [44,45] also found that high loading of Phe was a proxy for petroleum contaminated wastewater and street runoff. Additionally, Adeniji et al [25] state that high loadings of Fluo and Chyr were generated from stormwater runoff and domestic wastewater discharge. In summary, PC1 was mainly associated with urban street runoff and municipal wastewater discharges.…”
Section: ) Identification Of Sources By Diagnostic Binary Pah Isomer Ratiosmentioning
confidence: 99%
“…Regarding the quantitative analytical methods for PAHs in sediment samples, the most frequently used methods are GC/MS, and HPLC coupled with UV/Fluorescence detectors. The considerations for choosing a suitable instrumental technique include sensitivity, selectivity, polarity of target compounds, and ability to isolate PAH isomers [25]. Diagnostic ratios of PAHs, such as the anthracene/(anthracene+phenanthrene) ratio, the benzo[a]anthracene / benzo[a]anthracene + chrysene) ratio, and the fluoranthene / (fluoranthene + pyrene) ratio, have been used to identify the likely parent sources of PAHs in a number of studies [6][7][8]26].…”
Section: Introductionmentioning
confidence: 99%